Assessing physicians' knowledge, attitude, and practice on anticoagulant therapy in non-valvular atrial fibrillation: Syrian insights - Sarya Swed; Haidara Bohsas; Hidar Alibrahim; Mohamad Nour Nasif; Yasmeen Abouainain; Nagham Jawish; Angela Ishak; Bassel Dibah; Eva Mahmoud; Suzanne Mahfoud; Bisher Sawaf; Wael Hafez; et al. (SpringerOpen, 2024)
Abstract Background Atrial fibrillation (AF) is the most prevalent cardiac condition linked to increased mortality due to complications such as stroke. Oral anticoagulant (OAC) is the mainstay in preventing cerebrovascular accidents in patients with AF. Recent evidence identified gaps in physician's knowledge in diagnosing and managing patients with AF. This study aims to assess Syrian physicians' knowledge, attitude, and practices regarding the use of anticoagulant therapy in non-valvular AF (NVAF) patients. A cross-sectional study was conducted using a validated web-based questionnaire, which included 56 items separated into four sections that collected information about demographics, knowledge, attitude, and practices. Chi-square and Kruskal Wallis were performed to analyze the statistical relationships between the knowledge, attitude, practice, and demographic variables. Results A total of 497 participants completed the survey, of which 62.6% were between the ages of 25 and 35. The average participant scores for knowledge, attitude, and practices were (48.18 ± 21.57), (81.54 ± 9.26), and (62.83 ± 12.42), respectively. Participants who demonstrated good understanding, a positive attitude, and good practices were 22.3%, 87.3%, and 25.4%, respectively. The fear of bleeding was identified as the most significant barrier to initiating anticoagulant medication in AF patients (55.5%). Doctors who attended training had a better knowledge score than those who did not (mean ± S.D. = 57.24 ± 20.7). Participants who stated that over 70% of their AF patients use aspirin received the highest attitude score (mean ± S.D = 86.98 ± 21.17). PhD participants reported higher practice scores than those with other educational backgrounds (mean ± S.D = 73.96 ± 11.3). Conclusion This research showed that primary care physicians in Syria had optimistic views regarding OAC therapy, suggesting that training interventions targeting physicians may lead to improvement in the treatment of patients with NVAF in Syria.